The impact of the financial crisis on the insurance sector and policy responses (Paris : OECD, 2011)
This special report assesses the impact of the crisis on the insurance sector and reviews policy responses within OECD countries. It is based to a large extent on a quantitative and qualitative questionnaire that was circulated to OECD countries in 2009. The report shows that generally the insurance sector demonstrated resilience to the crisis, though with some variation across the OECD, and concludes with a number of policy conclusions.
Foreword; Table of Contents; Introduction; Impact of the Financial Turmoil; Governmental and Supervisory Responses to the Crisis in the Insurance Sector; Key Policy and Regulatory Issues in the Insurance Sector; Key Policy Conclusions from the Crisis; Annex A Policy and Regulatory Responses to the Financial Crisis.